The Influence of demographic variables on the prevalence and severity of tooth wear in a Trinidadian population - Marchan, Shivaughn Maria; Rafeek, Reisha N.; Smith, William A. J. (Frontiers in Oral Health, 2025)
IntroductionThis study aimed to assess the prevalence and severity of wear in a Trinidadian adult patient population based on the demographic variables of age, sex and ethnicity.MethodsSecondary data, stored in an institutional repository as an SPSS file were re-coded. Age was re-coded to stratify the sample into five age groups. A new variable denoting the overall severity of tooth wear was added using the highest score for any examined tooth surface. Data for sex and ethnicity was not re-coded. Likelihood ratios on cross-tabulated data with an alpha level of 0.05 were used to ascertain significant differences in the overall severity of tooth wear for demographic variables. Cross-tabulations were also completed between demographic variables and individual scores for each examined surface in the upper and lower anterior sextants.ResultsThere was a highly statistically significant association (p < 0.01) between age and the overall severity score of tooth wear in this sample patient population with 64% of 18–30-year-olds having no wear while only 22% of the over 60 age range showed no wear. There were no significant associations on cross-tabulated data for the overall severity score of wear and sex or ethnicity (p > 0.05). However, data on tooth wear of specific tooth surfaces when cross-tabulated with sex and gender showed significant associations (p < 0.05).ConclusionAge appears to influence the prevalence and severity of overall wear. The severity of wear on the incisal edges of specific teeth appears to be influenced, in part, by the demographic variables of sex and ethnicity.